TINGKAT KEPATUHAN MINUM OBAT PADA PASIEN RAWAT JALAN SKIZOFRENIA DI WILAYAH KERJA PUSKESMAS X KABUPATEN TASIKMALYA - Sidik, Hasbi Muhammad; Alifiar, Ilham; Salasanti, Citra Dewi (Jurnal Farmasi & Sains Indonesia, 2025)
Schizophrenia is a chronic mental condition characterized by communication disturbances, impaired reality perception, abnormal emotional behavior, and cognitive function impairment. According to the WHO in 2022, there are approximately 24 million people with schizophrenia worldwide, with the highest prevalence in East Asia (8 million), followed by South Asia (4 million) and Southeast Asia (2 million). In Indonesia, the 2018 Riskesdas survey reported a prevalence of 6.7% for schizophrenia per 1000 households. This study aims to determine the extent of medication adherence among outpatient schizophrenia patients in the working area of Health Center X in Tasikmalaya Regency. The observational method with a cross-sectional approach was used, where data were prospectively collected through interviews using the Medication Adherence Rating Scale (MARS) questionnaire. The study subjects consisted of 13 respondents who were schizophrenia patients receiving treatment at Health Center X in Tasikmalaya Regency. The research findings indicate that 9 out of 13 respondents had high adherence levels, while the remaining 4 had low adherence levels. Factors such as gender, age, education level, occupation, and marital status did not significantly influence medication adherence.